Influence of Vanadium on the Microstructure and High Temperature Properties of Semi High-Speed steel TIG Cladding Layer - ZHANG Yong, GE Ze-long, TANG Jia-cheng, QI Xiu-ling (Cailiao Baohu, 2021)
Aim at promoting the development of semi high-speed steel rolls remanufacturing technology, based on the alloy systems of semi high-speed steel, the influences of vanadium addition in argon arc welding powders on the high-temperature properties and weldability of cladding layer were studied.In addition, the effect of vanadium addition on the formability of welding seam was explored throng welding process test.The means of metallographic observation and XRD were employed to study the effect of vanadium addition on the cladding layer microstructure.Furthermore, high temperature oxidation and red hardness tests were carried out to clarify the effect of vanadium addition on the high temperature properties of cladding layer.Results showed that adding vanadium could modify the formability of cladding layers and improve their high-temperature oxidation resistance, red hardness and thermal fatigue resistance.